Using the LANCA® Model to Account for Soil Quality Within LCA: First Application and Approach Comparison in Two Contrasted Tropical Case Studies - Alexis Thoumazeau; Céline Bustany; Jérémy Rodrigues; Cécile Bessou (Indonesian Life Cycle Assessment Network (ILCAN), 2019)
Assessing the effect of land management on soil quality is nowadays a key environmental concern, as the soil system is linked to major ecosystem services. There is a strong methodological shortage to integrate the impact of anthropogenic pressure on the soil system within large scale environmental frameworks, such as the Life Cycle Assessment. The LANCA® method was proposed to meet this need, integrating five impact categories of soil functions and directly applicable within the Life Cycle Assessment framework. Although the most recent 2016-LANCA® version shows readiness to be integrated in this large scale environmental framework to meet the demand, it has not yet been applied and validated on case studies. This study proposes a first application of the LANCA® model on two contrasted agricultural-based case studies to share experience in implementing the model through both background and foreground approaches, to analyze the first model outputs and to provide tracks for further model improvements. The results proved that both LANCA® approaches were poorly sensitive to the agricultural land managements tested. The foreground approach was difficult to implement due to the lack of transparency of the targeted characterization factors calculation procedure. Further global sensitivity and redundancy analysis should also be proposed in order to validate the consistency of the global model.